2020
DOI: 10.1021/acsbiomaterials.9b01946
|View full text |Cite
|
Sign up to set email alerts
|

Gr/TiO2 Films with Light-Controlled Positive/Negative Charge for Cell Harvesting Application

Abstract: Light-induced cell harvest shows much potential in in vitro cell culture. In this work, a light-responsive monolayer graphene (Gr)/titanium dioxide nanodot (TN) film is designed and used for light-induced cell harvest. It is found that after 20 min of 365 nm UV or 450 nm visible light illumination, different types of cells could be detached from the surface effectively. The highest cell detachment ratio reaches about 95%. The mechanism of such a cell detachment is contributed to light illumination generates ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Under UV or visible light illumination for 20 minutes, negative or positive charges were accumulated on the Gr/TN film respectively, which changed the conformation of extracellular matrix (ECM) molecules to a more disordered state, ultimately resulting in cell detachment. 68 However, limited studies on the in situ UV light-responsive strategy were little more than in vitro cell (1) Photocatalysis producing ROS (PDT) (1) PDT and/or PTT for antibacterial or anti-tumor applications 23,26,30,[39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]66,69 (2) Incorporating photosensitive molecules (PDA, RP, IR780 and etc.) 23,30,39, (2) Photo-triggered hyperthermia (PTT)…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under UV or visible light illumination for 20 minutes, negative or positive charges were accumulated on the Gr/TN film respectively, which changed the conformation of extracellular matrix (ECM) molecules to a more disordered state, ultimately resulting in cell detachment. 68 However, limited studies on the in situ UV light-responsive strategy were little more than in vitro cell (1) Photocatalysis producing ROS (PDT) (1) PDT and/or PTT for antibacterial or anti-tumor applications 23,26,30,[39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]66,69 (2) Incorporating photosensitive molecules (PDA, RP, IR780 and etc.) 23,30,39, (2) Photo-triggered hyperthermia (PTT)…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
“…(2) Photocatalysis-mediated controlled release 36,37 (3) Fabricating heterojunctions [67][68][69] (3) Heterojunctions induced photoelectric effects…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Other elements incorporated into these TiO 2 films include SiO 2 , Zn, and Gr, resulting in the spontaneous and rapid detachment of functionally intact cell sheets. [60][61][62] Moreover, TiO 2 film surfaces decorated using organic materials have been utilized, as in the case of two studies demonstrating that TiO 2 films with surface-immobilized RGD peptides can improve the adhesion of cells while allowing for rapid cell sheet detachment within 30 min upon UV (365 nm) irradiation. 63,64 A 2017 study explored the use of recombinant human laminin-521 to modify TiO 2 films and found that an intact cell sheet characterized by improved proliferation and adhesion could be attained using this strategy.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
“…Exposure to UV might affect cell functions, which is a potential concern. On the other hand, the electrical charge of culture surfaces can be controlled by UV or even via visible light exposure, and cell sheets can be harvested because of the changed electrical charge [ 29 ]. This is because, when the electrical charge changes from negative to positive, electrostatic repulsion occurs between the cell membranes and culture surfaces, both with a positive charge.…”
Section: Cell Sheet Fabrication Technologiesmentioning
confidence: 99%